Metagenomics analysis of red blood cell and fresh‐frozen plasma units. Issue 7 (11th May 2017) - Lau, Pierre; Cordey, Samuel; Brito, Francisco; Tirefort, Diderik; Petty, Thomas J.; Turin, Lara; Guichebaron, Arthur; Docquier, Mylène; Zdobnov, Evgeny M.; Waldvogel‐Abramowski, Sophie; Lecompte, Thomas; Kaiser, Laurent; et al.
Abstract : BACKGROUND: Although the risk of transmitting infectious agents by blood transfusion is dramatically reduced after donor selection, leukoreduction, and laboratory testing, some could still be present in donor's blood. A description of metagenomes in blood products eligible for transfusion represents relevant information to evaluate the risk of pathogen transmission by transfusion. STUDY DESIGN AND METHODS: Detection of viruses, bacteria, and fungi genomes was made by high‐throughput sequencing (HTS) of 600 manufactured blood products eligible for transfusion: 300 red blood cell (RBC) and 300 fresh‐frozen plasma (FFP) units. RESULTS: Anelloviruses and human pegivirus, frequent in the blood of healthy individuals, were found. Human papillomavirus type 27 and Merkel cell polyomavirus, present on the skin, were also detected. Unexpectedly, astrovirus MLB2 was identified and characterized in a FFP unit. The presence of astrovirus MLB2 was confirmed in donor's blood and corresponded to an asymptomatic acute viremia. Sequences of bacteria and fungi were also detected; they are likely the result of environmental contamination. CONCLUSION: This study demonstrates that HTS is a promising tool for detecting common and less frequent infectious pathogens in blood products